2024
DOI: 10.1149/2754-2726/ad3561
|View full text |Cite
|
Sign up to set email alerts
|

Review—Smart Wearable Sensors for Health and Lifestyle Monitoring: Commercial and Emerging Solutions

N. M. Cusack,
P. D. Venkatraman,
U. Raza
et al.

Abstract: The rapid growth of urbanisation has brought about various health concerns for citizens living in urban environments. Sedentary lifestyles, increased pollution levels, and high levels of stress have become prevalent issues affecting the overall well-being of urban populations. In recent years, the emergence of smart wearable devices has offered a promising avenue to address these health concerns and promote healthier lifestyles. This review evaluatse the effectiveness of smart wearables in mitigating health co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…This indicates a significant advancement in diagnostic capabilities, offering a more nuanced and potentially transformative approach to disease identification and monitoring. [29][30][31][32] A nitrate sensing system has been reported that utilizes exhaled breath condensate (EBC) as a biosample to monitor and diagnose asthma. The process involves collecting exhaled breath in a medicated polypropylene bag, which is then cooled to form nitrate condensate.…”
Section: Current Statue: Potential Of Optical Modules In Disease Diag...mentioning
confidence: 99%
“…This indicates a significant advancement in diagnostic capabilities, offering a more nuanced and potentially transformative approach to disease identification and monitoring. [29][30][31][32] A nitrate sensing system has been reported that utilizes exhaled breath condensate (EBC) as a biosample to monitor and diagnose asthma. The process involves collecting exhaled breath in a medicated polypropylene bag, which is then cooled to form nitrate condensate.…”
Section: Current Statue: Potential Of Optical Modules In Disease Diag...mentioning
confidence: 99%
“…Clinical trials are necessary to assess the efficacy of nanoenabled optical biosensors in various real-world scenarios, including patient groups, sample types, and clinical settings. Investigations are underway to determine how well nanoenabled optical biosensors can identify AMR infections and how accurately they can provide information on the best antibiotic therapy. These investigations aim to enhance patient outcomes by proving the clinical viability and usefulness of intelligent sensing in directing personalized and targeted antimicrobial treatment. Nanosensors can potentially revolutionize the AMR field but must address several challenges before being utilized in clinical settings.…”
Section: Clinical Status Of Intelligent Sensing In Nanoenabled Optica...mentioning
confidence: 99%
“…CDs molecules exhibit a distinct cupshaped chemical configuration, 23 rendering them suitable for the development of the stochastic signal. Synthesis of new materials, 24,25 and utilisation of electrochemical sensors for point-of-care diagnostics [26][27][28] contributed in the past years to the improving of tools used in biomedical analysis for fast diagnosis of various diseases.…”
mentioning
confidence: 99%